The Progress of Chitosan-Based Nanoparticles for Intravesical Bladder Cancer Treatment - Chong Yu; Shuai Wang; Wing-Fu Lai; Dahong Zhang (MDPI AG, 2023)
Bladder cancer (BC) is the most frequently occurring cancer of the urinary system, with non-muscle-invasive bladder cancer (NMIBC) accounting for 75-85% of all the bladder cancers. Patients with NMIBC have a good survival rate but are at high risk for tumor recurrence and disease progression. Intravesical instillation of antitumor agents is the standard treatment for NMIBC following transurethral resection of bladder tumors. Chemotherapeutic drugs are broadly employed for bladder cancer treatment, but have limited efficacy due to chemo-resistance and systemic toxicity. Additionally, the periodic voiding of bladder and low permeability of the bladder urothelium impair the retention of drugs, resulting in a weak antitumoral response. Chitosan is a non-toxic and biocompatible polymer which enables better penetration of specific drugs to the deeper cell layers of the bladder as a consequence of temporarily abolishing the barrier function of urothelium, thus offering multifaceted biomedical applications in urinary bladder epithelial. Nowadays, the rapid development of nanoparticles significantly improves the tumor therapy with enhanced drug transport. This review presents an overview on the state of chitosan-based nanoparticles in the field of intravesical bladder cancer treatment.